2015
DOI: 10.1007/s10096-015-2506-7
|View full text |Cite
|
Sign up to set email alerts
|

Number of positive blood cultures, biofilm formation, and adhesin genes in differentiating true coagulase-negative staphylococci bacteremia from contamination

Abstract: The significance of the number of coagulase-negative staphylococci (CNS)-positive blood cultures remains obscure in regards to determining true bacteremia versus contamination. The goal of this study was to determine the predictors of real CNS bloodstream infection among intensive care unit (ICU) patients. ICU patients with at least one CNS-positive blood culture were identified from the microbiology database. Biofilm formation was tested by glass tube and microtiter plate assay. mecA gene, ica operon genes (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…To overcome the risk of contaminations, we only counted CoNS infection as "true", when infants additionally had clinical signs of infection and an elevated laboratory marker [42].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the risk of contaminations, we only counted CoNS infection as "true", when infants additionally had clinical signs of infection and an elevated laboratory marker [42].…”
Section: Discussionmentioning
confidence: 99%
“…Based on several studies, it was observed that commensal strains seem to be more susceptible to antibiotics [496], often positive to the genes aap and fdh and the ACME element [154,[496][497][498] and repeatedly negative to the biofilm-associated genes icaA and bhp and the IS256 [499,500]. In the case of clinical isolates, it has been often linked to higher antibiotic resistance and the presence of the genes icaA and bhp, as well as the carriage of the IS256 and SCCmec elements [496][497][498][501][502][503].…”
Section: Diagnosticsmentioning
confidence: 99%
“…These microorganisms may include Gram-negative bacteria such as Escherichia coli , Pseudomonas aeruginosa , Klebsiella species , Neisseria meningitidis , and Haemophilus influenzae , and Gram-positive bacteria such as coagulase-negative staphylococci (CoNS), Staphylococcus aureus , Streptococcus pneumoniae , Streptococcus pyogenes , Streptococcus agalactiae , and Enterococcus faecium [12]. The incidence of bloodstream infection is attributed to ageing of patients on admission, increasing number of patients with compromised immunity, and the acquisition of virulence factors by bloodstream pathogens [13, 14] as well as factors linked to infection prevention and control measures and implementation [15]. Bloodstream infections can be categorized into three groups based on its mode of occurrence: in immunocompetent host with intact defenses, in patients at the extremes of life, and in patients affected by pathological conditions putting them at risk to the infections [11].…”
Section: Introductionmentioning
confidence: 99%